Chromosomal characteristics of the temperate notothenioid fish Eleginops maclovinus (Cuvier) - F. MAZZEI; J. P. COUTANCEAU; HW DETRICH III; V. PRIRODINA; C. OZOUF COSTAZ; GHIGLIOTTI, LAURA; PISANO, EVA (Springer Verlag, 2008)
The Falkland’s mullet, Eleginops maclovinus, is the only modern representative of the Sub-Antarctic family Eleginopidae, suborder Notothenioidei. Based on specimens from the Falkland Islands/Islas Malvinas, the Magellan Straits, and the southern coast of Chile, we have established the specific karyotype by conventional cytogenetic methods and have mapped the chromosomal loci of the ribosomal genes by fluorescence in situ hybridization (FISH). With respect to the basal notothenioid family Bovichtidae and to the hypothetical basal condition of the suborder (diploid number = 48, fundamental number = 48), E. maclovinus displays a slightly derived karyotype (diploid number = 48, fundamental number = 54). In contrast to the bovichtids, the 45S and 5S ribosomal DNAs are co-localized to a single chromosome pair. Condensation of the ribosomal genes to a single locus is likely to represent an intermediate stage in the evolution of notothenioid karyology. Features unique to E. maclovinus (e.g., morphology of its large, rDNA-bearing chromosome pair) probably result from divergence during the long evolutionary isolation of the family.